2014
DOI: 10.1590/1414-431x20143240
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin D1 expression in prostate carcinoma

Abstract: The purpose of this study was to investigate the relationship between cyclin D1 expression and clinicopathological parameters in patients with prostate carcinoma. We assessed cyclin D1 expression by conventional immunohistochemistry in 85 patients who underwent radical prostatectomy for prostate carcinoma and 10 normal prostate tissue samples retrieved from autopsies. We measured nuclear immunostaining in the entire tumor area and based the results on the percentage of positive tumor cells. The preoperative pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 23 publications
5
9
0
Order By: Relevance
“…In this study, the relation between Gleason Scoring and Cyclin D1 expression were in harmony to previous reports, showing a positive relationship between the expression of Cyclin D1 and Gleason score, especially with high-grade tumors [8,22,[29][30][31]. While in comparison to other studies, no association was found [29,33,34].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In this study, the relation between Gleason Scoring and Cyclin D1 expression were in harmony to previous reports, showing a positive relationship between the expression of Cyclin D1 and Gleason score, especially with high-grade tumors [8,22,[29][30][31]. While in comparison to other studies, no association was found [29,33,34].…”
Section: Discussionsupporting
confidence: 89%
“…Correspondingly to previous reports [8,[29][30][31][32], that stated a significant association especially with high-grade tumors, in this study the reported correlation of Cyclin D1 and Gleason score was statistically significant (P value= 0,001). While in another study expression of Cyclin D1 in BPH was not detected [31], and in another study, although Cyclin D1 is expressed in BPH, rarely Cyclin D1 is overexpressed in cases of PC [26].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…As well, due to the predictive preoperative usefulness of the Gleason score correlated with Cyclin D1 expression to predict tumor behavior, it became easy to differentiate between malignant and benign disease [37,38]. However, in some studies, Gleason score did not satisfy that theme [8,[39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…Over-expression of cyclin D1 shortens the G1-S transition, thus promoting tumorigenesis and cancer recurrence in diverse human cancers [229,230]. In PCa, cyclin D1 expression is upregulated and correlated with high-grade Gleason score [231]. Cyclin D1 also leads to transformation of androgen-independent state through the upregulation of MDM2 [232].…”
Section: Cyclin D1mentioning
confidence: 99%